THE EFFECTIVENESS OF SHARIA ECONOMIC DISPUTE RESOLUTION BETWEEN RELIGIOUS COURT AND NATIONAL SHARIA ARBITRATION BOARD - Aziz, Muhammad Abdul; Sasongkojati, Fardan Bintang Agung (Universitas Muhammadiyah Surakarta, 2022)
Sharia economic dispute can be resolved through litigation or judicial and non-litigation or out-of-court lines. Resolution disputes through religious courts always takes a long time and complicated administration, but until now is it still in high demand by justice seekers. There is dispute resolution outside the judiciary, one of which is arbitration through National Sharia Arbitration Board (BASYARNAS) which can be the solution. This paper is a qualitative research study with a case was taken from Religious Court Class 1A Sleman and BASYARNAS Representative In Yogyakarta. The findings of this study provide the results dispute resolution in religious courts is more desirable because it has more executive powers than BASYARNAS, and also religious courts hold the absolute authority of sharia economic dispute resolution and religious courts spread throughout districts in Indonesia, so religious courts are very easy to find, in contrast to BASYARNAS whose existence is still in every capital of several provinces in Indonesia. Religious courts are superior because of the quality of judges, their presence in every district in Indonesia, and the culture of the people.